ANALYSIS OF HUMAN RESOURCES AND DIGITAL LEADERSHIP IN DEVELOPING DIGITAL TALENT AT PT. TELKOM - R. Rifa Herdian; M. Syamsul Maarif; Anggraini Sukmawati; Irman Hermadi (Jurnal Mebis, 2024)
This study investigates the impact of knowledge sharing on sustainable performance with employee ambidexterity as a mediator. A survey was conducted with 200 employees from various organizations in Indonesia. The results suggest that knowledge sharing has a positive impact on sustainable performance, and employee ambidexterity mediates the relationship between knowledge sharing and sustainable performance. These findings suggest that organizations should encourage knowledge sharing among employees and develop employee ambidexterity to improve sustainable performance.